Effect of nitrogen and phosphorus on seed yield and uptake of nutrients in musk mallow (Abelmoschus moschatus Medic.) - Agashe, S S Wanjari, S G Wankhade, P P Khode, M R Kale, S A (Journal of Spices and Aromatic Crops, 2005)
A field experiment conducted at Akola (Maharashtra) to study the effect of nitrogen and phosphorus on seed yield and uptake of nutrients in musk mallow (Abelmoschus moschatus) indicated that application of 75 kg N ha-1 and 50 kg P2O5 ha-1 recorded significantly higher seed yield and nutrient (NPK) uptake. The maximum uptake of nitrogen was registered at 135 days after sowing and phosphorus and potassium uptake at 180 days after sowing.